Effects of Environment-Based Learning on Elementary Students’ Knowledge and Environmental Attitudes in Science Education - Nursamsi Nursamsi; Erma Suryani Sahabuddin; Nur Abidah Idrus (Program Studi PGSD FIP UNM, 2026)
This study investigated the effects of environment-based learning on elementary students’ knowledge and environmental attitudes in science education. A quantitative approach with a quasi-experimental design was employed. The participants consisted of 32 fifth-grade students at UPT SPF SD Negeri Kassi, Makassar, Indonesia, divided into an experimental group (n = 16) and a control group (n = 16). The experimental group received science instruction through an environment-based learning model, while the control group was taught using conventional learning methods. Data were collected through observation sheets, knowledge tests, and attitude questionnaires. The data were analyzed using descriptive statistics and independent sample t-tests. The findings revealed that the implementation of the environment-based learning model was conducted effectively, with observation scores increasing from the good to the very good category. Students in the experimental group demonstrated higher posttest scores in both knowledge and environmental attitudes compared to those in the control group. Statistical analysis showed significant differences between the two groups, indicating that the environment-based learning model positively influenced students’ learning outcomes. The findings suggest that integrating environmental contexts into science instruction enhances students’ conceptual understanding and promotes positive environmental attitudes. Therefore, environment-based learning can be considered an effective instructional approach for improving both cognitive and affective outcomes in elementary science education.